Standardization of F-18 by digital b-(LS)-g coincidence counting - Rodrigues Ferreira Maltez, Dario Pablo (2011)
The nuclide 18F disintegrates to 18O by β + emission (96.86%) and electron capture (3.14%) with a half-life of 1.8288 h. It is widely used in nuclear medicine for positron emission tomography (PET). Because of its short half-life this nuclide requires the development of fast measuring methods to be standardized. The combination of LSC methods with digital techniques proves to be a good alternative to get low uncertainties for this, and other, short lived nuclides. A radioactive solution of 18F has been standardized by coincidence counting with a LSC, using the logical sum of double coincidences in a TDCR array and a NaI scintillation detector. The results show good consistency with other techniques like 4πγ and LSC.